MIcrospher-iiUM, a novel, controlled-released drug/gene delivery system - Mohamed, Farahidah; Doolanea, Abd Almonem; Harun Ismail, Ahmad Fahmi (IIUM Press, 2011)
Multiple-emulsion, solvent-evaporation method is employed to synthesise MICROSPHERiiUM. A biodegradable co-polymer, poly(L-lactic-co-glycolic acid) (PLGA), is used as the matrix to form the microspheres. Briefly, an appropriate amount of PLGA is dissolved in dichloromethane to form the primary emulsion. This phase is then homogenised with on aqueous phase, containing surfactant and a model drug (e.g. plasmid DNA or small molecules drug) for a certain duration and at an appropriate speed. The resultant waterin- oil-in-water (w/o/w) emulsion is then dispersed in a bigger volume of aqueous stabiliser. Then the mixture is transferred to a continuously stirred hardening tank containing the same stabiliser. Stirring is continued for a certain duration to allow complete evaporation of the solvent. The hardened MICROSPHER-iiUM isharvested by means of centrifugation and washing with distilled before it was freeze-dried. Characterisation of the MICROSPHERiiUM is conducted to investigate its surface morphology, size distribution, encapsulation efficiency and in-vitro release profile. Different protocols are adopted depending on the types of the madel drug to analyse the model drug. This MICROSPHER-iium has demonstrated robustness in encapsulating different types of agents with substantial encapsulation efficiency. The controlled-release profile is also achievable due to the inherent degradation rate of the co-polymers, PLGA, of which the rate and duration are dependent on its molecular weight. The colloidal size of this delivery system and the release of drug that can be controlled are envisaged to enhance the quality of therapy in chronic diseases as it can improve patient compliance towards drug regiment owing to reduction in frequency of dosing and reduction in side effects.